Sodium zirconium cyclosilicate suspension and methods of making same
Patent Information
- Application Number
- CN202610457290.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-08
- Filing Date
- 2026-04-08
- Publication Date
- 2026-10-16
AI Technical Summary
实际在使用过程中药物粉末极易沉淀,沉淀后的药物粉末极难再次分散
1. 本发明提供的混悬液,能够稳定存储至少1年,几乎无沉降。
Smart Images

Figure CN122911896A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of pharmaceutical preparations, specifically to a sodium zirconium cyclosilicate suspension and its preparation method. Background Technology
[0002] Hyperkalemia is an electrolyte disorder that can damage neuromuscular and gastrointestinal functions, lead to arrhythmias, and in severe cases, endanger life.
[0003] Patients with hyperkalemia often also experience renal failure, requiring dialysis 1-2 times per week. Dialysis patients need to limit their daily water intake to approximately 200ml, depending on the frequency of dialysis. Excessive water intake increases the body's water volume burden, potentially triggering hypertension and heart failure. Currently, the marketed dosage form is sodium zirconium cyclosilicate powder (Libezhuo®), available in 5g / sachet and 10g / sachet formats. Patients are instructed to pour 5g of the medication completely into a glass of approximately 45ml of water, stir thoroughly, and then drink. If the powder settles, it should be stirred again to ensure all the medication is ingested. However, in practice, the powder easily settles and is extremely difficult to disperse again. Furthermore, a large amount of gritty powder residue remains in the mouth after administration, requiring patients to drink water to remove it, significantly impacting patient compliance and safety.
[0004] Furthermore, during the correction phase, the drug instructions recommend a starting dose of 10g, three times a day. Based on this, the normal daily water intake would exceed 135mL, which is more than half of the daily water intake for dialysis patients, placing a heavy burden on the patient's kidneys.
[0005] Chinese patent CN116617159A discloses an oral suspension of sodium zirconium cyclosilicate and its preparation method. The oral suspension of sodium zirconium cyclosilicate, by mass percentage, consists of 10-30% sodium zirconium cyclosilicate, 0.1-2.0% cellulose, 0.01-0.30% suspending agent, 0-10% flavoring agent, 0-1.0% preservative, and purified water. The suspension prepared by this formula has a high viscosity, and heating is required during filling to reduce its viscosity, which increases the difficulty of filling during production.
[0006] Chinese patent CN117919173A discloses an oral suspension of sodium zirconium silicate and its preparation method. The oral suspension of sodium zirconium silicate is composed of sodium carboxymethyl cellulose, colloidal silica, flavoring agent, preservative and purified water according to the mass formula. The sodium carboxymethyl cellulose is used as a flocculant. After homogenization with sodium zirconium silicate and silica, it quickly flocculates and precipitates. After flocculation and precipitation, it is extremely difficult to redisperse. Its essence is no different from the clinical use of commercially available sodium zirconium silicate powder (Libezhuo®). Moreover, it is very easy to accumulate in the filling pump pipeline during the filling process, which makes normal production impossible and commercial production impossible.
[0007] In summary, the clinical need is for a sodium zirconium silicate suspension that requires less water, is safer, does not stratify or settle during long-term storage, has a stable filling process, can be commercially produced, and is bioequivalent to the marketed sodium zirconium silicate powder (Libezhuo®). Summary of the Invention
[0008] Therefore, the technical problem to be solved by the present invention is to overcome the defects in the prior art, thereby providing a sodium zirconium cyclosilicate suspension, wherein the suspension is an aqueous phase, the active ingredient is sodium zirconium cyclosilicate, and the suspending agent is magnesium aluminum silicate and one or more polymeric suspending agents.
[0009] Preferably, the polymeric suspending agent is selected from one or more of xanthan gum, gelatin, carrageenan, carbomer, hydroxypropyl cellulose, hydroxypropyl methylcellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, microcrystalline cellulose and sodium carboxymethyl cellulose co-treated product, microcrystalline cellulose and guar gum co-treated product, and hydroxypropyl guar gum, and more preferably xanthan gum.
[0010] The suspension contains 0.2 g to 0.3 g / mL of sodium zirconium cyclosilicate, preferably 0.25 g / mL.
[0011] The magnesium aluminum silicate is of type I magnesium aluminum silicate.
[0012] The weight ratio of sodium zirconium silicate, magnesium aluminum silicate, and polymeric suspending agent is as follows: for every 100 parts of sodium zirconium silicate, there are 2-20 parts of magnesium aluminum silicate and 0.2-2.0 parts of polymeric suspending agent. Preferably, for every 100 parts of sodium zirconium silicate, there are 3-12 parts of magnesium aluminum silicate and 0.3-1.6 parts of polymeric suspending agent.
[0013] The present invention further provides a drug packaging, wherein the contents of the drug packaging are the suspension described in the present invention, and the drug packaging is in the form of a bag containing 2.5g, 5g or 10g of sodium zirconium cyclosilicate per bag, or in the form of a bottle containing an integer multiple of 2.5g of sodium zirconium cyclosilicate per bottle.
[0014] The suspension according to claim 1, wherein the pH value of the suspension is 5.0-7.5.
[0015] Preferably, the viscosity of the suspension was tested using the viscosity determination method of Appendix 0633, Part IV of the Chinese Pharmacopoeia 2020, under the condition of rotor No. 3 at 30 revolutions.
[0016] The sodium zirconium cyclosilicate has the molecular formula: Na ~1.5 H ~0.5ZrSi3O9•2-3H2O, with over 95% being in the ZS-9 crystal form. Since the drug "Sodium Zirconium Cyclosilicate Powder" is already on the market, and its structure and properties are common knowledge, the active ingredient in this invention is referred to as "Sodium Zirconium Cyclosilicate."
[0017] The magnesium aluminum silicate IC described in this invention is also known as magnesium aluminum silicate HV, and the pharmacopoeia name “magnesium aluminum silicate IC” is used in this invention.
[0018] The suspending agent described in this invention refers to an excipient that maintains the stability of a suspension by increasing the viscosity of the dispersion medium and reducing the sedimentation rate of particles.
[0019] The term "polymer" refers to compounds with a molecular weight exceeding 1000. Examples include xanthan gum, gelatin, carrageenan, carbomer, hydroxypropyl cellulose, hydroxypropyl methylcellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, microcrystalline cellulose and sodium carboxymethyl cellulose co-processed products, microcrystalline cellulose and guar gum co-processed products, and hydroxypropyl guar gum. Those skilled in the art will readily understand that, based on the technical field and applications of this invention, pharmaceutically acceptable polymeric suspending agents should be used, such as excipients permitted in the pharmacopoeias of China, the United States, Europe, and Japan.
[0020] The suspension may also contain one or more other pharmaceutically acceptable excipients, such as flavoring agents, preservatives, and pH adjusters, to improve flavor and extend shelf life.
[0021] The present invention does not specifically limit the type of flavoring agent, and it can be any pharmaceutically acceptable excipient well known to those skilled in the art. As an example, the flavoring agent may be selected from maltitol, sucralose, or flavorings.
[0022] The preservative primarily functions to prevent the deterioration of high-molecular-weight suspending agents such as xanthan gum, thus facilitating long-term preservation. The preservative is selected from one or more parabens, such as methylparaben or propylparaben.
[0023] The pH adjuster refers to an acid, base, or buffer used to adjust and stabilize pH, selected from one or more of citric acid, sodium citrate, and sodium hydroxide.
[0024] Preferably, the pH of the suspension should be between 5.0 and 7.5. Excessive acidity may damage the sodium zirconium cyclosilicate skeleton structure, while excessive alkalinity is detrimental to the stability of xanthan gum and preservatives. Furthermore, alkaline solutions have an astringent taste, making them difficult for patients to swallow.
[0025] The present invention also provides a method for treating hyperkalemia, comprising providing a patient with the sodium zirconium cyclosilicate suspension described in the present invention.
[0026] The technical solution of this invention has the following advantages: 1. The suspension provided by the present invention can be stored stably for at least one year with almost no sedimentation.
[0027] 2. The suspension provided by this invention has low viscosity, is easy to fill during production, and does not easily adhere to the container wall during use, which can reduce the loss of drug efficacy and also prevent patients from drinking extra water.
[0028] 3. The suspension provided by this invention is bioequivalent to the commercially available sodium zirconium cyclosilicate powder (Libezo®), making it convenient for patients to switch medications.
[0029] 4. The preferred embodiment of this invention has a better taste and less drug residue in the mouth, eliminating the need for rinsing with water. Therefore, the amount of water needed to take this product is much less than that needed to take the powder, and this product improves patient compliance and reduces patient safety risks. Attached Figure Description
[0030] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0031] Figure 1 This is a photo of the product from Example 2 after it has been stored for 12 months. Figure 2 These are comparative photos of the volumetric sedimentation ratio of Test Example 1. From left to right, the batch numbers are Example 1, Example 2, Example 3, and Comparative Example 2. Figure 3 These are photos of the sedimentation of commercially available Libezo® suspensions after 30 minutes of standing. From left to right, the batch numbers are NK2088A, NH3072B, and NJ2035A. Figure 4-5 This is a linear graph of the in vitro equivalence test between Example 3 and commercially available sodium zirconium cyclosilicate powder (Libezo®) in Test Example 2; Figure 6 Photograph of the tipping experiment in Test Example 3; Figure 7 Photograph of the plastic measuring cup tilting experiment in Test Example 5. Detailed Implementation
[0032] The sodium zirconium cyclosilicate used in this invention was prepared according to Example 1 of CN118439624B, and the excipients were commercially available products.
[0033] Example 1 Prepare the following pharmaceutical composition (Formula 1).
[0034] Table 1
[0035] Specific preparation process: 1) Weigh 100.0g of purified water and heat it. Add 0.5g of sodium citrate and half the amount of citric acid, and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben, and stir until completely dissolved.
[0036] 2) Add 6g of magnesium aluminum silicate under heat preservation, stir and disperse, and then use a high shear homogenizer to disperse evenly to obtain solution 1.
[0037] 3) Take 30.0g of purified water, add 0.6g of xanthan gum while heating, and stir until completely swollen to obtain solution 2.
[0038] 4) Add solution 2 to solution 1, add 50g of sodium zirconium cyclosilicate, and stir to disperse.
[0039] 5) Add the remaining citric acid to adjust the pH of the suspension, add water to 200 mL, stir to disperse, and obtain the suspension.
[0040] Example 2
[0041] Prepare the following pharmaceutical composition (Formula 2).
[0042] Table 2
[0043] Preparation process: 1) Add 100.0 kg of purified water to a 500 L mixing tank and heat. Add 0.27 kg of methylparaben and 0.03 kg of propylparaben to the mixing tank and stir until completely dissolved.
[0044] 2) Add 15kg of maltitol and stir until completely dissolved.
[0045] 3) Under heat preservation, add 3 kg of magnesium aluminum silicate and stir to disperse to obtain solution 1.
[0046] 4) Add 16.0 kg of purified water to a 50 L stainless steel mixing tank, heat, add 0.3 kg of xanthan gum, and stir until completely swollen to obtain solution 2.
[0047] 5) Add solution 2 to solution 1, add 37.5 kg of sodium zirconium cyclosilicate while stirring, add purified water to 150 L, stir to disperse, and obtain a suspension.
[0048] 6) Fill into polyester / aluminum / polyethylene composite bags, each bag containing 2.5g of sodium zirconium cyclosilicate (10mL), or 5g of sodium zirconium cyclosilicate (20mL), or 10g of sodium zirconium cyclosilicate (40mL).
[0049] Example 3 Prepare the following pharmaceutical composition (Formula 3).
[0050] Table 3
[0051] Specific preparation process: 1) Add 400.0 kg of purified water to a 1500 L mixing tank and heat. Add 1.5 kg of sodium citrate and 3.6 kg of citric acid, and stir until completely dissolved.
[0052] 2) Add 1.08 kg of methylparaben and 0.12 kg of propylparaben, and stir until completely dissolved.
[0053] 3) Add 60 kg of maltitol and stir until completely dissolved.
[0054] 4) Under heat preservation, add 12kg of magnesium aluminum silicate to the liquid preparation tank. After the material is added, stir and disperse it.
[0055] 5) Add 1.2 kg of xanthan gum and stir until fully swollen.
[0056] 6) Add 150 kg of sodium zirconium cyclosilicate, add purified water to 600 L while stirring, and continue stirring to disperse.
[0057] 7) The liquid is filled into polyester bottles using a bottling line liquid filling machine, 120mL per bottle.
[0058] Examples 4-8 Prepare the following pharmaceutical composition.
[0059] Table 4
[0060] Specific preparation process (taking Example 4 as an example, and adjusting the amount of excipients in Examples 5-8 according to the process of Example 4): 1) Weigh 100.0g of purified water and heat. Add sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0061] 2) Under heat preservation, add 4g of magnesium aluminum silicate, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0062] 3) Take 30g of purified water, heat it, add 0.8g of xanthan gum, and stir until it is completely swollen to obtain solution 2.
[0063] 4) Add solution 2 to solution 1, and add 50g of sodium zirconium cyclosilicate while stirring, and stir to disperse.
[0064] 5) Add citric acid to adjust the pH of the suspension, add water to 200 mL, stir to disperse, and obtain the suspension.
[0065] Examples 9-10 Prepare the following pharmaceutical composition.
[0066] Table 5
[0067] Specific preparation process (taking Example 9 as an example, Example 10 refers to the process of Example 9 with adjustments to the amount and type of excipients): 1) Weigh 100.0g of purified water and heat. Add sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0068] 2) Under heat preservation, add 4g of magnesium aluminum silicate, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0069] 3) Take 30g of purified water, heat it, add 0.4g of sodium carboxymethyl cellulose, and stir until it is completely swollen to obtain solution 2.
[0070] 4) Add solution 2 to solution 1, and add 50g of sodium zirconium cyclosilicate while stirring, and stir to disperse.
[0071] 5) Add citric acid to adjust the pH of the suspension, add water to 200 mL, stir to disperse, and obtain the suspension.
[0072] Comparative Example 1 Referring to Example 5 of CN116617159A, the following pharmaceutical composition was prepared.
[0073] Table 6
[0074] Specific preparation process: 1) Preparation of drug solution 1: Take 50% (w / w) of purified water of the total amount of suspension, heat to 60~90℃ and keep constant temperature, add suspending agent and thickener, and use a homogenizer to make it fully swollen and mixed evenly.
[0075] 2) Preparation of drug solution 2: Take 10% (w / w) of purified water of the total amount of suspension, add flavoring agent and preservative, and make it completely dissolved in water.
[0076] 3) Mix drug solution 1 and drug solution 2 evenly, add sodium zirconium cyclosilicate, and use a homogenizer to stir to make it initially evenly mixed. Then add an appropriate amount of purified water for quantitative mixing, and continue stirring to make it fully mixed and evenly dispersed.
[0077] Comparative Example 2: Prepared according to the method described in Example 6 of Chinese Patent CN117919173 A, but using sodium zirconium cyclosilicate with a basically ZS-9 crystal form to ensure consistency with the sodium zirconium cyclosilicate in the example and facilitate comparison of suspension stability.
[0078] The pharmaceutical composition is formulated as follows: sodium zirconium cyclosilicate 50g; sodium carboxymethyl cellulose 0.5g; sucrose 2g; colloidal silica 0.1g; methylparaben 0.1g; add water to 100mL.
[0079] The preparation method is as follows: Disperse the prescribed amount of sodium carboxymethyl cellulose in 60 ml of purified water at room temperature, heat to 90 °C under stirring to swell and clarify, and cool to room temperature to obtain solution I; Add the prescribed amounts of sucrose and methylparaben to solution I, stir to dissolve, and obtain solution II; Add the prescribed amount of sodium zirconium cyclosilicate and colloidal silica to solution II, homogenize at 6000 rpm for 8 min, mix well, flocculate, and add water to 100 ml to obtain the finished sodium zirconium cyclosilicate oral suspension.
[0080] Comparative Example 3 Prepare the following pharmaceutical composition.
[0081] Table 7
[0082] Specific preparation process:
[0083] 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0084] 2) Add 15g of maltitol and stir until completely dissolved. 3) Under heat preservation, add 4g of magnesium aluminum silicate, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0085] 4) Take 30.0g of purified water, add 0.8g of xanthan gum, and stir until completely swollen to obtain solution 2.
[0086] 5) Add solution 2 to solution 1, stir, add 50g of sodium zirconium cyclosilicate, and stir to disperse.
[0087] 6) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0088] Comparative Examples 4-5 Table 8
[0089] Comparative Example 4: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0090] 2) Add 15g of maltitol and stir until completely dissolved.
[0091] 3) Under heat preservation, add 4g of magnesium aluminum silicate, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0092] 4) Add 50g of sodium zirconium cyclosilicate and stir to disperse.
[0093] 5) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0094] Comparative Example 5: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0095] 2) Add 15g of maltitol and stir until completely dissolved.
[0096] 3) Take an appropriate amount of purified water, add 0.8g of xanthan gum, and stir until completely swollen to obtain solution 2.
[0097] 4) Add solution 2 to solution 1, stir, add 50g of sodium zirconium cyclosilicate, and stir to disperse.
[0098] 5) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0099] Comparative Examples 6-7 Comparative Examples 6-7 investigated the synergistic effect of magnesium aluminum silicate and sodium carboxymethyl cellulose.
[0100] Table 9
[0101] Comparative Example 6: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0102] 2) Add 15g of maltitol and stir until completely dissolved.
[0103] 3) Under heat preservation, add 4g of magnesium aluminum silicate IC, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0104] 4) Take 30.0g of purified water, add 0.8g of sodium carboxymethyl cellulose, and stir until completely swollen to obtain solution 2.
[0105] 5) Add solution 2 to solution 1, stir, add 50g of sodium zirconium cyclosilicate, and stir to disperse.
[0106] 6) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0107] Comparative Example 7: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0108] 2) Add 15g of maltitol and stir until completely dissolved.
[0109] 3) Under heat preservation, add 4g of magnesium aluminum silicate IC, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0110] 4) Take 30.0g of purified water, add 0.8g of sodium carboxymethyl cellulose, and stir until completely swollen to obtain solution 2.
[0111] 5) Add solution 2 to solution 1, stir, add 0.4g Tween-80, and stir to disperse. Add 50g sodium zirconium cyclosilicate, and stir to disperse.
[0112] 6) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0113] Comparative Examples 8-9 Comparative Examples 8-9 investigated the synergistic effect of xanthan gum and magnesium aluminum silicate IB. Table 10
[0114] Comparative Example 8: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0115] 2) Add 15g of maltitol and stir until completely dissolved.
[0116] 3) Under heat preservation, add 8g of magnesium aluminum silicate IB, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0117] 4) Take 30.0g of purified water, add 0.4g of xanthan gum, and stir until completely swollen to obtain solution 2.
[0118] 5) Add solution 2 to solution 1, stir, add 50g of sodium zirconium cyclosilicate, and stir to disperse.
[0119] 6) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0120] Comparative Example 9: Specific preparation process: 1) Weigh 100.0g of purified water and heat. Add 0.5g of sodium citrate and stir until completely dissolved. Add 0.36g of methylparaben and 0.04g of propylparaben and stir until completely dissolved.
[0121] 2) Add 15g of maltitol and stir until completely dissolved.
[0122] 3) Under heat preservation, add 10g of magnesium aluminum silicate IB, stir and disperse, and use a high shear homogenizer to obtain solution 1.
[0123] 4) Take 30.0g of purified water, add 0.4g of xanthan gum, and stir until completely swollen to obtain solution 2.
[0124] 5) Add solution 2 to solution 1, stir, add 0.4g Tween-80, and stir to disperse. Add 50g sodium zirconium cyclosilicate, and stir to disperse.
[0125] 6) Add citric acid to adjust the pH of the suspension, add water to 200 mL and stir to disperse, thus obtaining the suspension.
[0126] Test Example 1: Referring to the viscosity determination method, Method 3, Appendix 0633 of the 2020 edition of the Chinese Pharmacopoeia, Volume IV, under conditions of 30 revolutions with a No. 3 rotor, and Appendix 0123, the finished oral suspensions of sodium zirconium cyclosilicate from Examples 1-10 and Comparative Examples 1-5 were measured respectively. The appearance, viscosity, potassium exchange capacity, and sedimentation volume ratio were examined at 0 days and long-term (25℃±2℃, 60%±5%RH) for 3-12 months. The appearance of Example 2 after 12 months is shown in [reference needed]. Figure 1 Settlement photographs of Examples 1-3 and Comparative Example 2 are shown below. Figure 2 For the sedimentation of commercially available Ribetron® after 30 minutes of clinical use, please refer to [link / reference needed]. Figure 3 .
[0127] Potassium ion exchange capacity (KEC) detection method: Accurately weigh an appropriate amount of potassium chloride of known purity, dissolve and dilute it with water to prepare a solution containing approximately 9.53 mg per ml, as a potassium ion stock solution. Accurately measure 1.0 ml of this solution into a 100 ml volumetric flask, dilute to the mark with water, and mix well to prepare a potassium ion reference solution. Take 10 ml of the sample to be tested (containing 2.5 g of sodium zirconium cyclosilicate), transfer it to a 100 ml volumetric flask, add 40 ml of the potassium ion stock solution, shake and mix for at least 3 hours, filter through a 0.45 μm microporous membrane, accurately measure 1.0 ml of the filtrate into a 100 ml volumetric flask, dilute to the mark with water, and mix well to prepare the test solution. The potassium ion exchange capacity (KEC) was determined by ion chromatography (Chinese Pharmacopoeia 2020 Edition, Part IV, General Chapter 0513) using a cation exchange column (Dionex lonPac CS12A 250*2mm column; or a column of equivalent performance). The detector was a conductivity detector (Dionex CERS 500e 2mm), the column temperature was 35℃, the mobile phase was 20 mmol / L methanesulfonic acid solution, and the flow rate was 1.0 mL per minute. Accurately measure 10 μL each of the test solution and the reference solution, inject them separately into the ion chromatograph, and record the chromatograms. Calculate the potassium ion exchange capacity (KEC) using the following formula.
[0128] The test results are summarized below.
[0129] Table 11
[0130] The results in the table above show that, using the formulation and process of this invention, the resulting sodium zirconium cyclosilicate suspension has a volumetric sedimentation ratio of over 0.99, and its potassium exchange capacity is consistent with that of commercially available Libezo®. The viscosities of the products in Examples 1-10 are all below 2000 centipoise, far less than that of Comparative Example 1, effectively solving the technical problem of filling difficulties caused by high viscosity and rapid flocculation and sedimentation during production, thus facilitating commercial production. It has been detected that the products in Examples 1-3 do not undergo sedimentation and stratification during long-term storage, indicating they can be stored for extended periods.
[0131] Compared with Example 1, the viscosity was too high, which was not conducive to filling.
[0132] Compared with Example 2, the product showed significant sedimentation after 30 minutes of standing, and could not be dispersed again after stirring, which was not conducive to filling and could not be stored for a long time.
[0133] The KEC content of the product in Comparative Example 3 showed a significant decrease, indicating that the framework of the ZS-9 crystal form was destroyed under low pH conditions, affecting the efficacy.
[0134] Comparative examples 4 and 5 demonstrate that neither magnesium aluminum silicate nor polymers alone can achieve stable suspension. The combination of the two shows excellent performance, enabling sodium zirconium cyclosilicate, which has a high density, to remain stably suspended for a long time, producing unexpected technical effects.
[0135] Test Example 2.
[0136] In vitro bioequivalence testing: The testing method is based on the FDA's Draft Guidance on Sodium Zirconium Cyclosilicate.
[0137] Equivalent index: The 90% CI of the ratio of the self-developed agent to commercially available sodium zirconium cyclosilicate K2 is 80~120%.
[0138] The test results are as follows.
[0139] Table 12
[0140] As shown in the table above, the 90% CI of the K2 ratio between the self-developed formulation (Example 3) and the commercially available sodium zirconium cyclosilicate powder (Libezo®) is 99.3%, which is within the range of 80-120%. Therefore, the self-developed formulation can be determined to be bioequivalent to sodium zirconium cyclosilicate powder (Libezo®). The patient's blood potassium level fluctuated less when changing medications, which is beneficial to medication safety.
[0141] Test Example 3 Taste evaluation was conducted using Example 3 and commercially available sodium zirconium cyclosilicate powder (Libezo®) according to the instructions for use. The evaluation method is as follows: (a) Evaluation Dimensions 1. Sweetness Medium sweetness (0-3 points): The sweetness is quite noticeable, and the taste is relatively pleasant.
[0142] No sweetness (4-6 points): The medicine has no sweetness and presents the original taste of the medicine.
[0143] Overly sweet (7-10 points): Too sweet and may make people feel uncomfortable.
[0144] 2. Smoothness Slight obstruction (0-3 points): There is no obstruction, no grainy or sticky feeling in the mouth.
[0145] Moderate obstruction (4-6 points): There is a slightly uncomfortable feeling, which may be due to tiny particles in the medication or a slight stickiness.
[0146] Severe obstruction (7-10 points): There is a noticeable obstruction when swallowing, requiring several swallows or drinking water to swallow completely.
[0147] 3. Grainy texture Slight graininess (0-3 points): You can feel very small particles, which do not affect the overall taste.
[0148] Medium granular texture (4-6 points): The granules are quite noticeable, and you can feel them rolling or rubbing in your mouth.
[0149] Strong grainy texture (7-10 points): The particles are large and rough, which will irritate the oral mucosa.
[0150] (II) Comprehensive Evaluation Criteria 1. Good (0-9 points): The overall taste is very good. The taste, smell and texture are all within an acceptable range, and there are no obvious unpleasant feelings.
[0151] 2. General (10-18 points): There are relatively obvious taste problems, such as a certain degree of resistance in the taste and texture, but the patient can still take it with some effort.
[0152] 3. Poor (19-30 points): The taste is very poor, with a strong sweetness or serious texture problems, which makes patients very reluctant to take it.
[0153] (III) Evaluation Results Table 13
[0154] Test Example 4 Pouring experiment See Figure 1 The suspension prepared in Example 3 was filled into 120 ml bottles. See also Figure 6 Open the 120mL bottle, invert it on a graduated cylinder for 5 minutes, and measure the volume of suspension that can be poured out. In Example 3, the product poured out was 119.5mL.
[0155] Test Example 5 Tilting test.
[0156] To simulate a patient's actual medication administration scenario, a plastic measuring cup was weighed as m1 = 4.6g, and 20mL of suspension was poured in (based on visual observation of the measuring cup's scale). The measuring cup was then weighed as m2 (28.8g of the product in Example 3). After tilting the measuring cup for 30 seconds, it was weighed again as m3 (5.4g of the product in Example 3). The container loss ratio was calculated to be (m3-m1) / (m2-m1)×100%=3.3%.
[0157] Using the product from Comparative Example 1, m2=28.6g, m3=12.5g. The container loss rate was 32.9%.
[0158] The results of this test case show that the product in Comparative Example 1 has excessive viscosity, which would result in significant loss of efficacy during actual medication administration, or require repeated scraping with a small spoon, making administration inconvenient. The product in Example 3 of this application has good flowability, facilitating precise oral administration.
[0159] See the comparison photos of the measuring cups after 30 seconds of pouring. Figure 7 (Left: Product of Example 3; Right: Product of Comparative Example 1). Test Example 6 Adult population trial.
[0160] Following the instructions for use of Ribedra (5g dispersed in 45ml of water), after taking Ribedra, spit it into a 500ml beaker. Rinse your mouth with purified water (15-25mL each time) and spit it into a 500ml beaker until there is no gritty feeling in your mouth. Record the amount of water used, filter and dry to obtain the amount of sodium zirconium cyclosilicate that was spat out.
[0161] Take 20 ml of the sample prepared in Example 3, spit it into a 500 ml beaker, rinse your mouth with purified water and spit it into a 500 ml beaker, record the amount of water used to completely eliminate the gritty feeling in your mouth, filter and dry to obtain the solid content, subtract the prescription amounts of magnesium aluminum silicate and xanthan gum to obtain the amount of sodium zirconium cyclosilicate.
[0162] Table 14
[0163] This test case simulates the process of a patient repeatedly rinsing their mouth and swallowing the medication after taking it to alleviate oral discomfort. Example 3 shows a good taste, mild astringency in the mouth, and requires less water intake. Furthermore, Example 3 exhibits good suspension properties and minimal residue buildup on the container wall, with a container wall loss (total amount minus spit-out amount) of 0.2-0.4g. In contrast, traditional suspension formulations experience container wall loss of 0.5-0.7g when the measuring cup is not thoroughly rinsed. This application demonstrates a significant advantage for the product.
[0164] Subjects reported that the product in Example 3 of this application had a smooth taste when taken, demonstrating that it leaves minimal residue in the patient's mouth. The effectiveness of this technology is corroborated by the results of the mouthwash water consumption test.
[0165] Test Example 7 Referring to Test Example 1, the stability of the products in Comparative Examples 6-9 was tested, and the results are shown in the table below.
[0166] Table 15
[0167] Comparative Examples 6 and 7 showed instability over long-term storage, demonstrating that although magnesium aluminum silicate and cellulose have a synergistic effect, their long-term suspension stability in the system is poor. Comparative Examples 8 and 9 showed acceptable short-term stability of magnesium aluminum silicate IB, but to achieve the same viscosity, the dosage of magnesium aluminum silicate IB was excessive, approaching the FDA-approved upper limit for safe dosage, posing a safety risk with long-term use.
[0168] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A sodium zirconium cyclosilicate suspension, characterized in that, The suspension is an aqueous phase, wherein the active ingredient is sodium zirconium cyclosilicate, and the suspending agent is magnesium aluminum silicate and one or more polymeric suspending agents.
2. The suspension according to claim 1, characterized in that, The polymeric suspending agent is selected from one or more of xanthan gum, gelatin, carrageenan, carbomer, hydroxypropyl cellulose, hydroxypropyl methylcellulose, carboxymethyl cellulose, sodium carboxymethyl cellulose, microcrystalline cellulose and sodium carboxymethyl cellulose co-treated product, microcrystalline cellulose and guar gum co-treated product, and hydroxypropyl guar gum, preferably xanthan gum.
3. The suspension according to claim 1, characterized in that, The suspension also contains one or more of the following: preservatives, flavoring agents, and pH adjusters.
4. The suspension according to claim 3, characterized in that, The preservative is selected from one or more parabens, and the pH adjuster is selected from one or more of citric acid, sodium citrate, and sodium hydroxide.
5. The suspension according to claim 1, characterized in that, The sodium zirconium cyclosilicate content in the suspension is 0.2g-0.3g / mL.
6. The suspension according to claim 1, characterized in that, The sodium zirconium cyclosilicate content in the suspension is 0.25 g / mL.
7. The suspension according to claim 1, characterized in that, The magnesium aluminum silicate is of type I magnesium aluminum silicate.
8. The suspension according to claim 1, characterized in that, The weight ratio of sodium zirconium cyclosilicate, magnesium aluminum silicate, and polymeric suspending agent is 2-20 parts magnesium aluminum silicate and 0.2-2.0 parts polymeric suspending agent per 100 parts sodium zirconium cyclosilicate.
9. The suspension according to claim 8, characterized in that, The weight ratio of sodium zirconium silicate, magnesium aluminum silicate, and polymeric suspending agent is 3-12 parts magnesium aluminum silicate and 0.3-1.6 parts polymeric suspending agent per 100 parts sodium zirconium silicate.
10. The suspension according to claim 1, characterized in that, The viscosity of the suspension was less than 2000 centipoise, as determined by the viscosity determination method of Method 3 (Appendix 0633) of the Chinese Pharmacopoeia 2020, under conditions of 30 revolutions per 30 rpm.
11. The suspension according to claim 1, characterized in that, The pH value of the suspension is 5.0-7.
5.
12. A drug packaging, characterized in that, The contents of the drug packaging are the suspension according to claims 1-10. The drug is packaged in bags, each containing 2.5g, 5g, or 10g of sodium zirconium cyclosilicate. Alternatively, it may be packaged in bottles, with each bottle containing an integer multiple of 2.5g of sodium zirconium cyclosilicate.
Citation Information
Patent Citations
Sodium zirconium cyclosilicate oral suspension and preparation method thereof
CN116617159A
Sodium zirconium cyclosilicate oral suspension as well as preparation method and application thereof
CN117919173A